Structural welding in bridges: Science mapping analysis and systematic review - Zhu, Jinsong; Wang, Ziyi; Tao, Youhai (Structures (Oxford), 2025)
Safety concerns related to structural welding in bridge design, construction, and maintenance have gained prominence due to the high costs of traffic disruptions and accidents. A thorough understanding of structural welding in bridges is essential for enhancing construction reliability and long-term operational resilience. As of December 2023, the first bibliometric analysis in this field, based on 1111 publications from the Web of Science, was conducted to assist researchers in understanding the frontiers and current trends in structural welding in bridges. This analysis produced a series of comprehensive knowledge maps covering research strengths, hotspots, trends, and foundational knowledge. Based on this, the literature was classified and graded, followed by a systematic evaluation. The study focuses on the research frontiers of intelligent structural welding in bridges from three aspects: research subjects, construction and operational technologies, and novel models. Future trends in intelligence were explored, and technology was introduced from artificial intelligence (AI) and digital twins (DT) to meet the safety requirements of welded bridge operations. Fracture mechanics, post-weld treatment, and machine vision are key technologies for ensuring the safety and quality of the bridge welded structure. This research provides a knowledge basis and implementation directions for intelligent structural welding research. Intelligent low-carbon construction for structural welding, AI-DT collaborative intelligent welding systems, and adaptive strategies for sophisticated bridge field welding are the focal points of attention in the future.